2017
DOI: 10.18632/oncotarget.19564
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated arginine deiminase can modulate tumor immune microenvironment by affecting immune checkpoint expression, decreasing regulatory T cell accumulation and inducing tumor T cell infiltration

Abstract: PEGylated arginine deiminase (ADI-PEG 20) is being investigated in clinical studies in arginine auxotrophic cancers and is well-tolerated. The anti-tumor properties of ADI-PEG 20 have been extensively investigated - ADI-PEG 20 inhibits the growth of auxotrophic cancers in vitro and in vivo - however, its impact on immune cells is largely unknown. Here we report the potential impact of ADI-PEG 20 on the tumor immune microenvironment. ADI-PEG 20 induced immunosuppressive programmed death-ligand 1 expression on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
5
28
0
Order By: Relevance
“…Metabolic fitness and T-cell survival are particularly crucial in anti-tumor responses. Only recently, Brin et al described no adverse side effects on human peripheral blood mononuclear cells upon arginine starvation [90]. This study thus supports recent findings stating that ADI-PEG20 does not significantly impair the viability of normal cells -especially when high amounts of citrulline are present [89].…”
Section: Arginine and The Complex Interplay With The Tumor Microenvirsupporting
confidence: 89%
See 2 more Smart Citations
“…Metabolic fitness and T-cell survival are particularly crucial in anti-tumor responses. Only recently, Brin et al described no adverse side effects on human peripheral blood mononuclear cells upon arginine starvation [90]. This study thus supports recent findings stating that ADI-PEG20 does not significantly impair the viability of normal cells -especially when high amounts of citrulline are present [89].…”
Section: Arginine and The Complex Interplay With The Tumor Microenvirsupporting
confidence: 89%
“…Though not clinically proven, ADI-PEG20 boosted tumor immunogenicity in a syngeneic B16-F10-melanoma mouse model and thus contradicts previous findings [90]. Effects were further enhanced when ADI-PEG20 was combined with immune-checkpoint inhibiting antibody PD-1 [90]. To the best of our knowledge, neither study examined the influence on antigen-presenting and antibody-producing B-cells in the context of arginine deprivation.…”
Section: Arginine and The Complex Interplay With The Tumor Microenvirmentioning
confidence: 61%
See 1 more Smart Citation
“…In the current study, we used an NAC concentration of no more than 20 mM; this concentration not only induced tumor cell death, but may also promote memory T cell proliferation. Recently, it was demonstrated that the ADI-PEG 20 enhances the response to anti-PD-1/PD-L1 in mouse models, with results suggesting a possible synergistic interaction [ 8 ]. Our current study shows that the efficacy of ADI-PEG 20 was enhanced in combination with NAC, suggesting that the combination of ADI-PEG 20, NAC, and anti-PD-1/PD-L1 blockade may be a promising therapeutic approach for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of arginine was assessed using ADI-PEG20 inhibitor ( 157 ). It can inhibit cell proliferation in vitro and tumor growth in vivo and decrease Treg accumulation ( 158 ). However, it would be more pertinent to prevent amino acid depletion by tumor cells or myeloid cells rather than decreasing amino acid rates in the TME.…”
Section: Targeting Metabolism For Efficient Immunotherapymentioning
confidence: 99%